SPEECH ACTS IN EMILY IN PARIS SEASON 1 EPISODE 1 - Chintia Handayani; Meriska Yosiana (Asosiasi Dosen Muda Indonesia, 2024)
This research examined about speech acts in the movie. Speech acts are the most widely examined object in language pragmatics. The most essential thing in speech act is the message that the speaker wants to be delivered. This research is aimed to analyse the speech acts in Emily in Paris, season 1: episodes 1 used the theory from Searle. This research used qualitative method in collecting the data. The result of the research shows that there are 50 data of speech act used in Emily in Paris, Season 1: Episodes 1. They are 21 data of Assertive, 7 data of Directive, 10 data of Commissive, 10 data of Expressive, and 2 data of Declarative. The findings show that the Assertive data are the most dominant used in this movie.